Analytical Study on Egyptian Inheritance Law Reform (Faraidh) - Saed Arthos; Muhammad Iqbal; Sukri Sukri (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
The decline of Muslims became the background for the birth of reform ideas. This can be seen with the birth of various figures who are aggressively voicing reforms in various fields, such as politics, education and law. History has recorded names such as Jamaluddin al-Afgani with Pan-Islamism, Muhammad Abduh with education reform, and Rasyid Ridho with the idea of legal dynamics. Which in turn has an impact on the modernization of the writing and learning system of Islamic law and the laying of Islamic law in state legislation. Islamic law, especially inheritance law, is practiced by Muslims in Indonesia on the basis of personal awareness and encouragement of faith and obedience to Islam. This law uses the main sources of the Qur'an and Hadith, which are complemented by Ijtihad and qiyas carried out by scholars and judges. The history of Islamic law reform cannot be separated from the dialectic of evolution that occurred from time to time, geographical scope and conditions. The main model of this movement is in the spirit of spreading and implementing Islamic law which emphasizes progressive efforts in the legal field with the spirit of reform. The spirit of renewal through the idea of reforming Islamic law, especially in the field of family law, occurred in the middle of the second decade of the 20th century in Turkey. This enthusiasm continued to give birth to brilliant ideas in the progress of law formation, one of which was followed by the birth of a mandatory will on the application of inheritance law issues in Egypt in order to meet the state's needs for the codification of family law regulations.